2003
DOI: 10.1103/physrevb.68.153107
|View full text |Cite
|
Sign up to set email alerts
|

ac field-induced quantum rectification effect in tunnel junctions

Abstract: We study the appearance of directed current in tunnel junctions (quantum ratchet effect), in the presence of an external ac field f (t). The current is established in a one-dimensional discrete inhomogeneous "tight-binding model". By making use of a symmetry analysis we predict the right choice of f (t) and obtain the directed current as a difference between electron transmission coefficients in opposite directions, ∆T = T LR − T RL . Numerical simulations confirm the predictions of the symmetry analysis and m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Also, that the harmonic functions appearing in the scaling laws are independent of har 1 is a consequence of the invariance of V under time translation. As expected, one finds that such scaling laws are quite general, i.e., they confirm and explain previous results for a great diversity of systems [7,14,15,22,25] subjected to a biharmonic force f h1,h2 (t). I now discuss how the aforementioned scaling laws change when the violation of the time-reversal symmetry of the system's dynamic equations cannot be absorbed in the temporal force.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Also, that the harmonic functions appearing in the scaling laws are independent of har 1 is a consequence of the invariance of V under time translation. As expected, one finds that such scaling laws are quite general, i.e., they confirm and explain previous results for a great diversity of systems [7,14,15,22,25] subjected to a biharmonic force f h1,h2 (t). I now discuss how the aforementioned scaling laws change when the violation of the time-reversal symmetry of the system's dynamic equations cannot be absorbed in the temporal force.…”
supporting
confidence: 89%
“…of the biharmonic force f h1,h2 (t) in leading order for the usual case [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]24,25] of small amplitudes (1/ǫ 1,2 → ∞). For the sake of clarity, consider first the case where the violation of the time-reversal symmetry of the system's dynamic equations can be absorbed in the temporal force because dissipation is negligible and the Lagrangian (Hamiltonian) of the system does not contain any additional term explicitly breaking the time-reversal symmetry.…”
mentioning
confidence: 99%
“…Other wave equations can be considered as well, and the ratchet concept can be adapted likewise to any other sort of physical current. For instance, the symmetry analysis was applied to the energy current generated by a nonlinear field equation which describes a long Josephson junction [160,161,162]. The predicted symmetry breaking was linked to the presence of solitons, and the corresponding soliton ratchet was subsequently successfully realized experimentally with a fluxon trapped in an annular Josephson junction which was driven by a microwave field [163].…”
Section: Extensions and Outlookmentioning
confidence: 99%
“…It was shown that not only the strength of the ac force but also its phase is of experimental relevance [20,21]. The generalization of the monochromatic ac force to a multi-frequency ac force leads to nontrivial results in ultra cold atom dynamics [22][23][24][25][26][27][28][29][30][31][32][33]. The relationship between symmetries and transport was explored for a cold atom ratchet with multifrequency driving [25].…”
mentioning
confidence: 99%